Design, Construction and Testing of Hydraulic Oil Press for Groundnut Oil Extraction (Global Journal of Science Frontier Research, 2020)
This paper presents the design, construction and testing of a hand operated hydraulic oil press for groundnut oil extraction. The device consists of a pressure cylinder, pressure plates, hand operated hydraulic press and oil collector. The maximum design pressure of the device is put at 16.2N/mm2 with groundnut holding capacity of approximately 1kg per batch. Materials for the construction of the device were selected to meet the design, safety, cost and service requirements of the device. Stainless steel was used for pressure cylinder, pressure plates and collector to avoid contamination of the oil while mild steel was used for constructing the frame. Other tools like steel rule/measuring tape and hacksaw for taking measurements and cutting of materials while vanier caliper for measurement of internal and external diameters of the pressure cylinder, plates and collector. The drilling and lathe machines were employed for drilling finishing, boring, and turning operations. The joining of parts was achieved using electric welding. Roasted groundnut seed is place between the layers of the pressure plates and the driven hydraulic press is used to compress the groundnut in the pressure cylinder to extract the oil which is then collected through the collector. The pressure cylinder consists of holes in which the extracted oil flows out of the cylinder. The press is released and the cylinder is taken away from the collector and the residual is removed with a press rod when the oil stops coming out. Test result show that an average weight of 0.2049kg oil is obtained from appropriately 1kg weight of roasted groundnut seeds which gives 21.8% of oil yield efficiency and extraction efficiency of 48.3% with an extraction loss of 0.33%. Considering the oil content of groundnut as 45%, it indicates that the simple hydraulic press could be effective in the oil extraction process with minimum extraction loss. It is recommended that it could be produce in relatively large number for usage in rural and semi-urban areas with no electricity to replace the traditional method while an electrically operated hydraulic press could facilitates small to medium scale businesses with improve capacity and efficiency.
Keywords: hydraulic oil press; oil yield; extraction efficiency; improve capacity and efficiency